Issues and Challenges in the Implementation of a Structure of the Observed Learning Outcomes (SOLO)-Based Formative Assessment in the Division of Northern Samar - Pialago, Chando S. (International Journal of Research in Interdisciplinary Studies, 2025)
This study explored the issues and challenges in the implementation of structured of the observed learning outcomes (SOLO) formative assessments among secondary schools in the Division of Northern Samar. Using qualitative research design, interviews and classroom observations were conducted among teachers who were purposively sampled from the 3 areas of the division namely pacific, central, and balicuatro to unearthing their experiences in the conduct of SOLO-based formative assessments. The saturated noteworthy statements in the thematic analysis formed global themes which are instructional constraints in assessment implementation, learner readiness and comprehension gaps, and alignment and resource limitations. It was concluded that challenges in implementing SOLO-based assessments stem from systemic barriers like time constraints, limited resources, and insufficient training. Teachers are willing but struggle with feasibility, especially in designing higher-level tasks. Sustained capacity-building is essential for successful implementation. With this, school heads may strengthen support by allowing more time for assessment planning, reducing teacher workload, and providing relevant materials. Teachers also need training in language-sensitive assessment to create accessible, cognitively rigorous tasks.